1959
DOI: 10.1161/01.res.7.6.943
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on the Origin of T-Waves Based on Determinations of Effective Refractory Period from Epicardial and Endocardial Aspects of the Ventricle

Abstract: The effective refractory period was determined at the surface and in the deeper layers of the dog heart and was correlated with the surface T-waves. A small delay in recovery of cardiac excitability appeared at the surface when T-waves were negative and in the deeper layers when T-waves were positive. Acute injury produced by ligation of the coronary artery caused a marked acceleration of recovery in the deeper layers, sometimes extending to the surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

1959
1959
2004
2004

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…In this study, we recorded MAPs from multiple endocardial and epicardial sites in the human ventricle in situ by means of the contact electrode technique.7 8 The contact electrode has a tip diameter of 1 14 In our study, the longest average APD was measured in the septal and diaphragmatic area and the shortest at anteroapical and posterolateral sites. There are no endocardial data from a large mammalian species with which to compare this gradient.…”
Section: Discussionmentioning
confidence: 77%
“…In this study, we recorded MAPs from multiple endocardial and epicardial sites in the human ventricle in situ by means of the contact electrode technique.7 8 The contact electrode has a tip diameter of 1 14 In our study, the longest average APD was measured in the septal and diaphragmatic area and the shortest at anteroapical and posterolateral sites. There are no endocardial data from a large mammalian species with which to compare this gradient.…”
Section: Discussionmentioning
confidence: 77%
“…It has been shown by several authors that repolarization is accelerated in myocardial fibers exposed to anoxia (25, 26) or after coronary occlusion (20). The second interpretation therefore seems preferable, although, in the present state of our knowledge, the two other hypotheses cannot be completely ruled out.…”
mentioning
confidence: 79%
“…Since the subendocardial temperature was essentially constant during this short period, it is reasonable to assume that if the 2 determinations could have been made simultaneously, the subendocardial effective refractory period would not have changed. When the data in this experiment were adjusted for the time required for excitation to spread from endocardium to epicardium, 1 it was found that when the T waves in the epieardial lead were negative, recovery at the epicardium was completed 2 msec, (not a significant difference) after that of the endocardium, but when the T waves were positive, it was completed 35 msec, before recovery of the endocardium. In 1 other animal in which a similar study was done, the T waves which were initially negative became positive when the epicardium became 7.2 C. warmer than the endocardium, as is shown in figure 5.…”
Section: Transmural Temperature Measurementsmentioning
confidence: 91%
“…N A previous publication, 1 it was shown that measurements of the effective refractory period were useful in following the time course of electrical recovery. Although this studj' was largely concerned with the local order of transmural recovery associated with negative T waves, a few observations during the acute phase of experimental infarction confirmed the fact that recovery was accelerated, especially in the deeper myocardial layers.…”
mentioning
confidence: 99%
See 1 more Smart Citation